أهمية البلاغة العربية في تفسير القرآن: The importance of Arabic rhetoric in the interpretation of the Qur’an - Shatabi, Ahmed (SIBAWAYH Arabic Language and Education, 2020)
The Qur’an, which is in Arabic, was revealed for two main purposes: the guidance of the people and the testimony to the sincerity of the prophecy of Muhammad (peace be upon him). This means that the Qur’anic verses from the beginning of their wall to the end are guidance and miracle. There’s no One of the verses of the Qur’an is both a guidance and a miracle. Because such guidance and miracle in the Qur’an are like one coin with two faces and cannot be separated. To separate them is equal to the death of the same spirit of the Qur’an. It is as if the guidance of the Qur’an is hidden behind its miracle, while miracles in which scholars do not differ in its eloquence. Guidance is the guidance that guides people to act or leave them, and this must be applied in the real world in everyday life in the form of actions to prove the guidance of the Qur’an. How can guidance be achieved and applied concretely without understanding the rhetoric, since it is the product of the Qur’an? It is therefore not a denier that eloquence is important in revealing the deepest meanings of the Qur’an, where it is guided. This desired disclosure will only be reached through an in-kind interpretation as a basic means.